Julius Caesar - Mankiewicz, Joseph L. (Warner Bros : Warner Home Videp, 2003)
"Hail Caesar!" cried the Roman legions. " Hail Julius Caesar! echoed critics and audiences alike for this rich entertainment that received five Academy Award nominations (including Best Picture), described by the National Board of Review and the editor Films in Review as the best and most forceful adaptation of William Shakespeare Hollywood has ever accomplished. John Gielgud, James Mason, Greer Garson and Deborah Kerr are among the superb players. And Marlon Brando, in a surprise casting, portrays defender of the republic Mark Anthony. Brando's convincing performance brought him the the third of four consecutive Best Actor Oscar nomination, and praise from The New York times." Bosley Crowther: "A major talent has emerged." Having withstood the test of time, Julius Caesar continues to bring the political- fighting and lust for power of a turbulent, blood-stained era to living, breathing screen life.